2012
DOI: 10.1182/blood-2011-06-359224
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-insensitive thromboxane biosynthesis in essential thrombocythemia is explained by accelerated renewal of the drug target

Abstract: Essential thrombocythemia (ET) is characterized by enhanced platelet generation and thrombotic complications. Oncedaily low-dose aspirin incompletely inhibits platelet thromboxane A 2 (TXA 2 ) in the majority of ET patients. In the present study, we investigated the determinants of aspirin-insensitive platelet TXA 2 biosynthesis and whether it could be further suppressed by changing the aspirin dose, formulation, or dosing interval. In 41 aspirin-treated ET patients, the immature platelet count predicted serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
214
0
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(231 citation statements)
references
References 47 publications
(95 reference statements)
9
214
0
8
Order By: Relevance
“…Histopathological studies in erythromelalgia have revealed platelet-rich arteriolar microthrombi with endothelial inflammation and intimal proliferation accompanied by increased platelet consumption that is coupled with abundant VW factor deposition [74][75][76]. In regards to aspirin therapy in PV or ET, a recent report suggested that twicedaily aspirin may work better than once daily dose in certain cases [77]. Accordingly, we sometimes consider such a therapeutic approach in patients who seem to be resistant to once daily dosing or considered to be at a higher risk of arterial thrombosis (Fig.…”
Section: Management Of Low-risk Pv or Et In The Absence Of Extreme Tmentioning
confidence: 99%
“…Histopathological studies in erythromelalgia have revealed platelet-rich arteriolar microthrombi with endothelial inflammation and intimal proliferation accompanied by increased platelet consumption that is coupled with abundant VW factor deposition [74][75][76]. In regards to aspirin therapy in PV or ET, a recent report suggested that twicedaily aspirin may work better than once daily dose in certain cases [77]. Accordingly, we sometimes consider such a therapeutic approach in patients who seem to be resistant to once daily dosing or considered to be at a higher risk of arterial thrombosis (Fig.…”
Section: Management Of Low-risk Pv or Et In The Absence Of Extreme Tmentioning
confidence: 99%
“…This is not entirely unexpected as previous studies have reported only marginal benefit of aspirin in the risk of recurrence of cardiovascular events in patients with ET and PV with a previous acute coronary syndrome [24]. This may be explained by the inadequate suppression of platelet TXA 2 production in patients with ET on once-daily low-dose aspirin [25]. A better platelet inhibition could be achieved by prescribing low-dose aspirin twice daily although this approach needs to be validated in prospective studies [26].…”
Section: Discussionmentioning
confidence: 63%
“…As patients on aspirin still get thrombosis, it has been challenged whether the thromboxane inhibition produced by low dose aspirin is sufficient, and data supporting this view have been reported [Dragani et al 2010;Pascale et al 2012]. Furthermore, adenosine diphosphate (ADP) receptor inhibition has been suggested as an additional therapeutic effort apart from thromboxane inhibition [Panova-Noeva et al 2013].…”
Section: Hemostasis and Cell Interactionmentioning
confidence: 99%